MASCULINITY IN JAVANESE PEOPLE: HOW DOES ARJUNA MASCULINITY DESCRIBE IN JAVANESE VERSION OF MAHABHARATA - Cerianing Putri Pratiwi; Fendy Yogha Pratama; Kundharu Saddhono (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
Masculinity in Javanese People: How does Arjuna Masculinity Describe in Javanese version of Mahabharata. Masculinity is a form of maleness construction toward man. Man is not just born with his masculinity naturally, instead it is formed by culture. In a puppetry figure, Arjuna figure is a description of man for Javanese people. Arjuna has a Javanese knight figure. This research, therefore, aims to find out and describe the masculinity of Arjuna’s character in Javanese Mahabharata story by Nano Riantiarno. Data used in the research is lingual units, which are sentences in discourses. The research data source uses a book entitled “Mahabarata Jawa (Javanese Mahabharata)” by Nano Riantiarno. The analysis technique is document analysis with interactive model as its data analysis technique. The research result indicates that there is a figure of Arjuna in the Javanese Mahabharata story that has masculinity characters. There are three masculinity characters of Arjuna, namely: Be a Big Wheel, Be a Sturdy, Give em Hell.